Financial Tourism: Exploring Trends and Patterns - Kadek Linda Kusnita; Gede Crisna Wijaya; I Made Dwi Darma Artanaya; I Wayan Aditya Tariana (Astina: Jurnal Ekonomi Utama, 2024)
Financial tourism, also known as financial travel or financial pilgrimage, refers to the trend of individuals or groups traveling to different countries or regions for the purpose of engaging in financial activities such as investment, banking, or seeking financial services. While financial tourism may offer benefits to individuals seeking favorable investment opportunities or financial services in other countries, it also has potential drawbacks. One opposing argument is that financial tourism can contribute to the destabilization of local economies. As individuals flock to foreign countries to take advantage of favorable interest rates or investment opportunities, this influx of capital can lead to inflationary pressures and create market imbalances. Additionally, it can also lead to exploitation of local financial systems and resources, leading to unequal distribution of wealth and exacerbating economic inequalities. These aspects of financial tourism raise concerns about its impact on the overall stability and sustainability of local economies. Furthermore, the rise of financial tourism is closely tied to globalization and the ease of international travel and communication. It is important to understand the trends and patterns of financial tourism in order to assess its potential impact on local and global economies. This reaserch aims to explore the current trends and patterns of financial tourism by conducting a comprehensive literature review. The literature review examines various sources to gain insight into the concept of financial tourism, its benefits and drawbacks, and its relationship with globalization.conclusion Based on the literature review, it is evident that financial tourism is a growing trend with both positive and negative implications for local and global economies. Financial tourism, also known as financial travel or financial pilgrimage, is a trend where individuals or groups travel to different countries or regions to engage in financial activities